Multiplexed, targeted profiling of single-cell proteomes and transcriptomes in a single reaction. Issue 1 (December 2016) - Genshaft, Alex; Li, Shuqiang; Gallant, Caroline; Darmanis, Spyros; Prakadan, Sanjay; Ziegler, Carly; Lundberg, Martin; Fredriksson, Simon; Hong, Joyce; Regev, Aviv; Livak, Kenneth; Landegren, Ulf; et al.
Abstract We present a scalable, integrated strategy for coupled protein and RNA detection from single cells. Our approach leverages the DNA polymerase activity of reverse transcriptase to simultaneously perform proximity extension assays and complementary DNA synthesis in the same reaction. Using the Fluidigm C1™ system, we profile the transcriptomic and proteomic response of a human breast adenocarcinoma cell line to a chemical perturbation, benchmarking against in situ hybridizations and immunofluorescence staining, as well as recombinant proteins, ERCC Spike-Ins, and population lysate dilutions. Through supervised and unsupervised analyses, we demonstrate synergies enabled by simultaneous measurement of single-cell protein and RNA abundances. Collectively, our generalizable approach highlights the potential for molecular metadata to inform highly-multiplexed single-cell analyses.